Physician-Controlled Wire-Guided Cannulation of the Minor Papilla. (27th July 2010) - Maple, John T.; Mansour, Lilah; Ammar, Tarek; Ansstas, Michael; Coté, Gregory A.; Azar, Riad R.
Abstract : Background . Minor papilla (MiP) cannulation is frequently performed using specialized small-caliber accessories. Outcomes data for MiP cannulation with standard-sized accessories are lacking. Methods . This is a case series describing MiP cannulation outcomes in consecutive patients treated by two endoscopists between July 2005 and November 2008 at two tertiary referral centers. MiP cannulation was attempted using a 4.4 Fr tip sphincterotome loaded with a0.03 5 ″, 260 cm hydrophilic-tip guidewire, using a wire-guided technique under physician control. Results . 25 patients were identified (14 women, mean age 45). Procedure indications included recurrent acute pancreatitis in 16 patients (64%) and chronic pancreatitis in 2 (8%), among other indications. MiP cannulation was successful in 24 patients (96%). Sphincterotomy followed by pancreatic stent placement was performed in 21 patients (84%). Mild post-ERCP pancreatitis occurred in 3 patients (12%). Conclusion . Physician-controlled wire-guided MiP cannulation using a 4.4 Fr sphincterotome and0.03 5 ″ guidewire is an effective and safe technique.